Surface Pre-Grouting Borehole Arrangement and Division of the Broken Roof of the Lower Seam of a Bifurcated Coal Seam. Issue 2 (March 2023) - Zhai, Xiaorong; Bi, Yaoshan; Hu, Ru; Jiwen, Wu; Hao, Hongjun
The coal roof of the lower seam of a bifurcated coal seam is always broken and is caused by the mining of the upper seam, which results in difficult support for the coal roof. This seriously affects the safe and efficient mining of the lower seam. Pre-grouting technology is often used to reinforce the regenerated roof in advance to improve its integrity of the roof. In this study, to provide a scientific basis for the layout of surface pre-grouting boreholes, the bifurcated coal seam at the Xutuan coal mine in the Huaibei mining area in China was analyzed. The height and depth of the damage in the coal roof and floor caused by upper seam mining were calculated using theoretical analysis and numerical simulation. The porosity and permeability of the goaf in different positions were calculated by numerical simulation, and the spatial distribution of the porosity and permeability and the slurry diffusion radius of different porosities were determined. Finally, the grouting section and layout of the pre-grouting boreholes were determined. Based on the design scheme, the drilling of the surface boreholes and the addition of the grouting were carried out. The accuracy of the theoretical analysis was verified by field drilling and grouting activity. The research results can provide a basis for the layout of surface pre-grouting boreholes and the selection of the grouting zone in areas of close-distance coal seam mining.